MSI2 deficiency in ILC3s attenuates DSS-induced colitis by affecting the intestinal microbiota - Li, Nengneng; Xu, Shiquan; Zhang, Shuaishuai; Zhu, Qiang; Meng, Xiaole; An, Wenbin; Fu, Baoqing; Zhong, Mengya; Yang, Yan; Lin, Zeyang; Liu, Xueni; Xia, Junjie; et al. (Frontiers in Immunology, 2023)
Background The etiology and pathogenesis of inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), are generally believed to be related to immune dysfunction and intestinal microbiota disorder. However, the exact mechanism is not yet fully understood. The pathological changes associated with dextran sodium sulfate (DSS)-induced colitis are similar to those in human UC. As a subgroup of the innate immune system, group 3 innate lymphoid cells (ILC3s) are widely distributed in the lamina propria of the intestinal mucosa, and their function can be regulated by a variety of molecules. Musashi2 (MSI2) is a type of evolutionarily conserved RNA-binding protein that maintains the function of various tissue stem cells and is essential for postintestinal epithelial regeneration. The effect of MSI2 deficiency in ILC3s on IBD has not been reported. Thus, mice with conditional MSI2 knockout in ILC3s were used to construct a DSS-induced colitis model and explore its effects on the pathogenesis of IBD and the species, quantity and function of the intestinal microbiota. Methods Msi2flox/flox mice (Msi2fl/fl) and Msi2flox/floxRorcCre mice (Msi2ΔRorc) were induced by DSS to establish the IBD model. The severity of colitis was evaluated by five measurements: body weight percentage, disease activity index, colon shortening degree, histopathological score and routine blood examination. The species, quantity and function of the intestinal microbiota were characterized by high-throughput 16S rRNA gene sequencing of DNA extracted from fecal samples. Results MSI2 was knocked out in the ILC3s of Msi2ΔRorc mice. The Msi2ΔRorc mice exhibited reductions in body weight loss, the disease activity index, degree of colon shortening, tissue histopathological score and immune cells in the peripheral blood compared to those of Msi2fl/fl mice after DSS administration. The 16S rRNA sequencing results showed that the diversity of the intestinal microbiota in DSS-treated Msi2ΔRorc mice changed, with the abundance of Firmicutes increasing and that of Bacteroidetes decreasing. The linear discriminant analysis effect size (LEfSe) approach revealed that Lactobacillaceae could be the key bacteria in the Msi2ΔRorc mouse during the improvement of colitis. Using PICRUST2 to predict the function of the intestinal microbiota, it was found that the functions of differential bacteria inferred by modeling were mainly enriched in infectious diseases, immune system and metabolic functions. Conclusions MSI2 deficiency in ILC3s attenuated DSS-induced colonic inflammation in mice and affected intestinal microbiota diversity, composition, and function, with Lactobacillaceae belonging to the phylum Firmicutes possibly representing the key bacteria. This finding could contribute to our understanding of the pathogenesis of IBD and provide new insights for its clinical diagnosis and treatment.